Dramatiser les savoirs ou le refus du clivage « matière-manière » dans les savoirs enseignés - Jonathan Philippe (Nantes Université, 2009)
Even if not always firmly based in theory, the conceptual distinction between the content of a lesson on one hand and the shape given to it by the method or style of the teacher on the other hand, is widely recognised. This distinction is problematic because, as soon as it is accepted (even tacitly), it precludes any useful understanding of how a piece of transferred knowledge is constructed by the teacher who is teaching it. Transferred knowledge contains multiple dimensions: it includes information, of course, but also certain requirements, references to specific gestures or actions, etc. This paper explores different aspects of transferred knowledge in order to show that a thorough analysis of the dynamics at work forces us to abandon the dichotomies of substance vs. form, content vs. method, or indeed matter vs. manner.